COVID-19 and homeschooling: factors of burden in women - Hernández, Daniel Antonio; Tezon, Mariana Inés (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The pandemic has increased the burden of household work for everyone, but women have been especially hard hit because of their traditional role as caregivers. As schools and childcare services closed, women were forced to assume responsibility for the education and care of children and other family members. In addition, increased economic uncertainty has led to women being primarily responsible for finding work and providing income for their families.